The Occupations of Free Women and Substitution with Enslaved Workers in the Antebellum United States - Barry R. Chiswick; RaeAnn H. Robinson (Global Labor Organization (GLO), 2022)
This paper analyzes the occupational status and distribution of free women in the antebellum United States. It considers both their reported and unreported (imputed) occupations, using the 1/100 IPUMS files from the 1860 Census of Population. After developing and testing the model based on economic and demographic variables used to explain whether a free woman has an occupation, analyses are conducted comparing their occupational distribution to free men, along with analyses among women by nativity, urbanization, and region of the country. While foreign-born and illiterate women were more likely to report having an occupation compared to their native-born and literate counterparts, they were equally likely to be working when unreported family workers are included. In the analysis limited to the slave-holding states, it is shown that the greater the slave-intensity of the county, the less likely were free women to report having an occupation, particularly as private household workers, suggesting substitution in the labor market between free women and enslaved labor.
Keywords: N31; J16; J21; J82; 330; Women; Labor Force Participation; Occupational Distribution; Unreported Family Workers; Enslaved Workers; Immigrants; 1860 Census of Population